Smart Energy Systems: The Need to Incorporate Homeostatically Controlled Microgrids to the Electric Power Distribution Industry : An Electric Utilities’ Perspective - Yanine, Fernando; Sanchez-Squella, Antonio; Barrueto, Aldo; Kumar Sahoo, Sarat; M. Cordova, Felisa (International Journal of Engineering and Technology, 2018)
For no one is a secret that nowadays electric power distribution systems (EPDS) are being faced with a number of challenges and concerns, which emanate not so much from a shortage of energy supply but from environmental, infrastructural and operational issues. They are required to preserve stability and continuity of operations at any time no matter what, regardless of what may occur in the surroundings. This is the true measure of what sustainable energy systems (SES) are all about and homeostaticity of energy systems seeks just that: to bring about a rapid, effective and efficient state of equilibrium between energy supply and energy expenditure in electric power systems (EPS). The paper presents the theoretical groundwork and a brief description of the model for the operation of SES and their role in energy sustainability, supported by theoretical and empirical results. The concept of homeostaticity in EPDS is explained, along with its role in SES.